Kinerja Guru Dipengaruhi oleh Kompetensi Guru dan Kepemimpinan Kepala Sekolah - Epa Epa (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
This study examines the optimization of teacher performance by measuring the effect of teacher competence and principal leadership on economic teacher performance. The method used is survey method and total sampling. The research subjects consisted of 55 high school economics teachers in the city of Tasikmalaya. Conclusion, teacher competence and principal leadership have a positive influence on teacher performance where the higher the teacher competence and the more effective the principal's leadership, it will improve the quality of teacher performance. Keywords: Teacher Competence, Teacher Performance, Principal Leadership